Gradual modification of ITO particle's crystal structure and optical properties by pulsed UV laser irradiation in a free liquid jet. Issue 18 (20th April 2017) - Lau, Marcus; Straube, Thomas; Aggarwal, A. Vikas; Hagemann, Ulrich; de Oliveira Viestel, Bernardo; Hartmann, Nils; Textor, Torsten; Lutz, Harald; Gutmann, Jochen S.; Barcikowski, Stephan
Abstract : Engineering of ITO particle properties by laser irradiation. Abstract : Indium tin oxide (ITO) particle coatings are known for high transparency in the visible, good conductive properties and near-infrared absorption. These properties depend on ITO particle's stoichiometric composition, defects and size. Here we present a method to gradually change ITO particle's optical properties by a simple and controlled laser irradiation process. The defined irradiation process and controlled energy dose input allows one to engineer the absorption and transmission of coatings made from these particles. We investigate the role of the surrounding solvent, influence of laser fluence and the specific energy dose targeting modification of the ITO particle's morphology and chemistry by stepwise laser irradiation in a free liquid jet. TEM, SEM, EDX, XPS, XRD and Raman are used to elucidate the structural, morphological and chemical changes of the laser-induced ITO particles. On the basis of these results the observed modification of the optical properties is tentatively attributed to chemical changes, e.g. laser-induced defects or partial reduction.